2011
DOI: 10.4041/kjod.2011.41.6.423
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional finite element analysis for determining the stress distribution after loading the bone surface with two-component mini-implants of varying length

Abstract: Objective: To evaluate the extent and aspect of stress to the cortical bone after application of a lateral force to a two-component orthodontic mini-implant (OMI, mini-implant) by using three-dimensional finite element analysis (FEA). Methods: The 3D-finite element models consisted of the maxilla, maxillary first molars, second premolars, and OMIs. The screw part of the OMI had a diameter of 1.8 mm and length of 8.5 mm and was placed between the roots of the upper second premolar and the first molar. The corti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Our results agree with those of Choi et al 5 , who used a lateral force of 2 N, also reporting that the stress in the adjacent bone increases with the increasing height of the miniscrew head and the point of application of force.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Our results agree with those of Choi et al 5 , who used a lateral force of 2 N, also reporting that the stress in the adjacent bone increases with the increasing height of the miniscrew head and the point of application of force.…”
supporting
confidence: 82%
“…MOI are perhaps the most versatile and most widely used of these devices, providing 'absolute anchorage' in three dimensional space in most cases. Furthermore, the ideal skeletal conditions for their placement (1-3), potential locations (4) and biomechanical properties (5) have been studied. Miniscrews may be made of type 5 titanium alloy (the most common), steel or lactic-glycolic.…”
Section: Introductionmentioning
confidence: 99%
“…The present study showed highest stresses on lateral incisors, and this may be due to the short roots of the lateral incisors [40]. Burstone and Viecilli [41] stated that it is a natural concept that larger teeth have more PDL and root support than smaller teeth, and hence, when the same load is applied, the stress magnitudes in the PDL for larger teeth are smaller and larger for smaller teeth.…”
Section: Discussionmentioning
confidence: 68%
“…5 Previously published literature has shown a positive correlation between the biomechanical characteristics of mini-screws and their in vivo performance. 5,11 The Temporary Anchorage Devices (TADs) placement torque (PT) is defined as the quantifiable measure of resistance to insertion of the anchorage device. It has been seen that the insertion torque is higher in the mandible compared to the maxilla, and there are more chances of failure of the TADs because of high torque during placement.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Several studies have been conducted on the clinical behavior of mini-screws and have concluded that a variety of factors such as type of mini-screws, dimensions, angle of insertion, insertion torque and force, placement site, and even proximity to roots are responsible for the success or failure of mini-screws. [5][6][7][8][9][10] Although the success of mini-screws can be attributed to multiple factors, primary stability has been shown to be of utmost importance. Primary stability of mini-screws is observed in bone remodeling, and it can be described as a favorable tissue response from the hard tissues.…”
Section: Introductionmentioning
confidence: 99%